INTELLECTUAL CAPITAL : PERSPEKTIF PENGAKUAN, PENGUKURAN DAN IMPLEMENTASI - Warno, Warno (Sekolah Tinggi Ilmu Ekonomi Semarang, 2011)
Intellectual capital is intangible corporate assets into an extremely valuable asset. As increasingly valuable intellectual capital as a company asset, providing a challenge for the accountants  to  be  able  to  identify,  measure  and  express  it  into  the  company's  financial statements. This is due to traditional accounting systems that have failed to disclose assets ini.Secara  general  intellectual  capital  is  divided  into  three  main  elements,  namely:  human capital that includes the knowledge and skills of employees, capital structure that includes technology and information infrastructure that supports it, costomer capital by building good relationships with consumers. These elements will interact dynamically, as well as continuous and wide so that it will generate value for companies In terms of measurement, there are many concepts of intellectual capital measurement that was developed by researchers today. But in general the methods developed can be grouped into two groups, namely: the measurement of non-monetary (non financial) and the measurement of the monetary (financial). From the measurement models are developed each have advantages and disadvantages, so that according to the authors to choose which model is most appropriate for use, an action that is not appropriate, because the measurement is simply a tool that can be applied to the situation and condition of the company with the specification certain. While the intellectual capital reporting is done by making measurements of non-monetary and report it as a supplement in the company's annual report. Such supplements are known by the term intellectual capital statement. Already there are some countries that reported intellectual capital in annual reports, for example, reports on the company's intellectual capital between Denmark, Sweden and the Australian